Experimental testing of innovative cold-formed "GEB" section = Badania eksperymentalne innowacyjnego kształtownika giętego na zimno typu "GEB" - Łukowicz, Agnieszka; Urbańska-Galewska, Elżbieta; Gordziej-Zagórowska, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the major advantages of light gauge steel structures made of cold-formed steel sections is their low weight so the production of typical single-storey steel structures of this kind of profiles is still rising. The well known profiles, e.o. Z-sections, C-sections and the so called hat-sections studied and described in the literature, are used mainly as purlins or truss components. A new profile GEB was patented for the use for primary load-bearing member in fabricated steel frames.
Keywords: przekroje gięte na zimno; kostrukcje stalowe; badania eksperymentalne; wytrzymałość na zginanie; cold-formed sections; steel structures; experimental research; bending capacity